School Scientific Argumentation: Model for the Defense of the Environment - Valenzuela-González, Adriana; Zuñiga-González, Laura (Universidad Pedagógica y Tecnológica de Colombia, 2019)
This research proposal is aimed to the approach, validation, implementation and evaluation of a scientific argumentation model that promotes the recognition of renewable energies as a strategy to reduce environmental problems in elementary school students of the Ciudad Verde Educational Institution, at the municipality of Soacha. A mixed type methodology is presented, with the intention of taking advantage of its qualitative and quantitative components. As a result, the theoretical elements that will allow the construction of the argumentative model proposal are generally described. The conclusion indicates the importance of developing argumentative processes that contribute to overcoming the global climate crisis. This, through educational actions that strengthen the development of critical thinking, so that citizens can contribute in a participatory way to the mitigation of current environmental problems.